Synergistic Control of Liquid Crystallinity and Phosphorescence in Gold(I) Complexes via Strategic Alkyl Chain Design - Arushi Rawat; Kohsuke Matsumoto; Ganesan Prabusankar; Osamu Tsutsumi (Crystals, 2025)
Liquid crystals exhibit unique properties that can be tailored in response to external stimuli. Significant research is directed toward the development of luminescent materials exhibiting liquid crystallinity for various applications. The present work reports Au(I) complexes featuring N-heterocyclic carbene and phenyl acetylide ligands. Metal complexes enable the utilization of the triplet excitons through their inherent spin–orbit coupling, promoting intersystem crossing from singlet (Sn) to triplet (Tn) states to observe room-temperature phosphorescence (RTP). The strong bonds between carbene and Au enhance the thermal stability, and the substituted benzimidazole ring alters the thermodynamic and photophysical properties of the complexes. Incorporating the acetylide ligands with long alkoxy chains led to the formation of liquid crystalline (LC) phases, which exhibited stability over a wide temperature range. Additionally, the luminescence behavior was affected by the ethynyl ligands, and high quantum yields of RTP were observed. This study establishes the development of LC Au(I) complexes with a thermodynamically stable LC mesophase over a wide temperature range for applications in the field of light-emitting functional materials.